Degradation of Methyldopa by Banana - Kiminori Mohri; Yoshihiro Uesawa (MDPI AG, 2010)
Methyldopa, an antihypertensive, is a very close analogue of DOPA. Drug interaction accompanied by degradation in a banana juice mixture was reported for DOPA. However, the effect of banana on methyldopa has not been reported. Therefore, we have investigated the impact of banana juice on methyldopa. The drug and supernatant of banana pulp were mixed, and the mixture was observed for changes in color, drug concentration, and ultraviolet-visible absorption spectra at 30 °C. The originally clear and colorless mixture started to acquire a yellow coloration after about 30 seconds after the mixing. The color tone increasingly deepened, then blistered solid particles that do not dissolve were observed after 3 hours. Concentration of methyldopa in the mixture decreased by 60% after 5 min, to 0.5% after 30 min of the mixing. From these findings, it was suggested that the drastic alterations were caused by banana polyphenol oxidase that plays a role in the biosynthesis of melanin pigment from levodopa in banana pulp. Because the degradation of methyldopa occurs extremely fast, it was suggested concomitant use of this anti-hypertensive and banana juice consumption should be avoided in clinical practice.